Pre‐Polymerization Enables Controllable Synthesis of Nanosheet‐Based Porphyrin Polymers towards High‐Performance Li‐Ion Batteries. Issue 46 (20th July 2020) - Han, Zhuolei; Ai, Yan; Jiang, Xiaolin; You, Yuxiu; Wei, Facai; Luo, Hao; Cui, Jing; Bao, Qinye; Fu, Jianwei; He, Qingguo; Liu, Shaohua; Cheng, Jiangong
Abstract: The precise regulation of nucleation growth and assembly of polymers is still an intriguing goal but an enormous challenge. In this study, we proposed a pre‐polymerization strategy to regulate the assembly and growth of polymers by facilely controlling the concentration of polymerization initiator, and thus obtained two kinds of different nanosheet‐based porphyrin polymer materials using tetrakis‐5, 10, 15, 20‐(4‐aminophenyl) porphyrin (TAPP) as the precursor. Notably, due to the π–π stacking and doping of TAPP during the preparation process, the obtained PTAPP‐nanocube material exhibits a high intrinsic bulk conductivity reaching 1.49×10 −4 S m −1 . Profiting from the large π‐conjugated structure of porphyrin units, closely stacked layer structure and excellent conductivity, the resultant porphyrin polymers, as electrode materials for lithium ion batteries, deliver high specific capacity (≈650 mAh g −1 at the current density of 100 mA g −1 ), excellent rate performance and long‐cycle stability, which are among the best reports of porphyrin polymer‐based electrode materials for lithium‐ion batteries, to the best of our knowledge. Therefore, such a pre‐polymerization approach would provide a new insight for the controllable synthesis of polymers towards custom‐made architecture and function. Abstract : A simple, gentle and effective pre‐polymerization strategy for controlled modulation of assembly and growth of porphyrin polymers was proposed. The resultant nanosheet‐based porphyrin polymers exhibited high intrinsic bulk conductivity, outstanding specific capacity, excellent rate performance and long‐cycle stability for lithium‐ion batteries (see figure).